Dietary Guide for Vesiculobullous Diseases: Literature Review - Bohkyeong Suh; Hamid Ahmed; Jasraj Sandhu; Rashidah Wiley (Taylor & Francis Group, 2024)
Background Oral vesiculobullous diseases (VBD) consist of disorders which result in blister formation. VBDs are considered to be a multifactorial disease process. Corticosteroids and immunomodulating drugs are used for disease management.Methods The research team assessed peer-reviewed journal articles related to the dietary details of oral lichen planus, mucous membrane pemphigoid, and pemphigus vulgaris. The articles included in this study comprised literature reviews, randomized controlled trials, case studies, and systematic reviews published in the last 26 years (1997-2023).Results The literature review revealed the promising role that nutrition plays in the management of VBD. Avoiding triggering food and maintaining a well-nourished diet can decrease the symptoms noted during active episodes of VBDs. Oral hygiene maintenance decreases the presence of infection which is beneficial to the recovery process.Conclusion Studies have shown that the addition of essential vitamins, minerals, and supplements to the diet can aid in the management of VBDs, however, further research is needed.Practical Implications Dental providers can use this guide as a way to educate patients on the dietary adjustments needed after the diagnosis of one of the vesiculobullous disorders.